What is math? - Dotlich, Rebecca Kai; Yoshikawa, Sachiko (New York : Little, Brown and Company, 2022)
"A rhyming picture-book introduction to math for the very young, with visual depictions of everyday STEM applications"-- Provided by publisher
Primary
Keywords: Mathematics -- Juvenile literature; Stories in rhyme